1999
DOI: 10.1046/j.1365-2133.1999.02974.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel anti-inflammatory drug, SDZ ASM 981, for the treatment of skin diseases: in vitro pharmacology

Abstract: SDZ ASM 981, a novel ascomycin macrolactam derivative, has high anti-inflammatory activity in animal models of allergic contact dermatitis and shows clinical efficacy in atopic dermatitis, allergic contact dermatitis and psoriasis, after topical application. Here we report on the in vitro activities of this promising new drug. SDZ ASM 981 inhibits the proliferation of human T cells after antigen-specific or non-specific stimulation. It downregulates the production of Th1 [interleukin (IL)-2, interferon-gamma] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
185
0
9

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(200 citation statements)
references
References 43 publications
6
185
0
9
Order By: Relevance
“…20,27,[30][31][32]44 The favorable safety and tolerability profile of 1% pimecrolimus cream demonstrated in published pediatric studies 35,[37][38][39]43,44 is supported by the data summarized in this review. The combined analysis of the results from 4 pharmacokinetic studies conducted with 35 infants with AD indicated that pimecrolimus blood concentrations after topical applications were consistently low, irrespective of the level of disease severity and percentage of TBSA involved.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…20,27,[30][31][32]44 The favorable safety and tolerability profile of 1% pimecrolimus cream demonstrated in published pediatric studies 35,[37][38][39]43,44 is supported by the data summarized in this review. The combined analysis of the results from 4 pharmacokinetic studies conducted with 35 infants with AD indicated that pimecrolimus blood concentrations after topical applications were consistently low, irrespective of the level of disease severity and percentage of TBSA involved.…”
Section: Discussionmentioning
confidence: 59%
“…The major concern with the use of 1% pimecrolimus cream is the fact that calcineurin inhibitors have immunosuppressive properties when administered systemically at high doses, although the immunosuppressive effects of systemically administered pimecrolimus are lower than those demonstrated with other drugs of the same class. 21 Therefore, it is important to confirm the preclinical and clinical data 20,26,[30][31][32] indicating that topical applications of pimecrolimus are associated with minimal systemic absorption and do not lead to adverse experiences attributable to its immunosuppressive potential. This issue should be addressed particularly among infants, because the risk of systemic absorption of topical drugs for these individuals is higher than that for older children and adults.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A maior parte dos pacientes apresentava DA leve e moderada e os resultados apontaram redução de intensidade da lesão, diminuição do prurido e, a longo prazo, diminuição do número e intensidade de novas crises. Há estudos em lactentes entre 3 e 23 meses que revelaram os mesmos benefícios encontrados em crianças maiores [26][27][28] 29 . Uma particularidade dos inibidores de calcineurina é sua especial eficácia em pescoço e face, sendo esta última uma região de risco para a utilização de corticoterapia tópica 30 .…”
Section: Eficácia Dos Inibidores De Calcineurinaunclassified
“…A freqüência de prurido no local da aplicação por vezes não superou os achados observados nos pacientes que utilizavam apenas o veículo. Entretanto, em comparação à corticoterapia, o ardor e o prurido observados foram maiores nos pacientes que utilizavam tacrolimo [26][27][28][29][30][31][32][33][34] .…”
Section: Efeitos Adversos Locaisunclassified